2002
DOI: 10.1038/sj/mp/4000986
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for the role of the dopamine D4 receptor (DRD4) gene in attachment disorganization: interaction of the exon III 48-bp repeat and the −521 C/T promoter polymorphisms

Abstract: Keywords: DRD4 exon III VNTR polymorphism; −521 C/T promoter polymorphism; attachment disorganization; dopamineIn non-clinical low-risk populations 15% of infants show disorganized attachment behavior 1,2 with their caregivers in the Strange Situation, 3 a mildly stressful laboratory procedure testing infants' ability to cope with separation anxiety. Disorganization of early attachment has been primarily ascribed to inadequate parenting, 2,4,5 and has been associated with childhood behavior problems 6,7 and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 14 publications
(28 reference statements)
3
71
1
1
Order By: Relevance
“…The attachment disorganization and DRD4 work was recently summarized well by Bernier and Meins [43], who posited a threshold approach to disorganization, arguing that when enough risk factors are encountered (genetic and environmental), disorganization results. A sample of Hungarian infants reported on by Gervai et al [44] and Lakatos et al [45,46] suggested that the 7-repeat DRD4 gene polymorphism could be a risk factor for disorganized attachment; specifically, the 7-repeat allele was observed in 71% of disorganized children in this sample, compared with only 29% of nondisorganized children. Further examination of the same sample revealed that this association was substantially enhanced when children also carried the -521T allele in the promoter region of the DRD4 gene [46].…”
Section: Advances In Relevant Gene-environment Considerationsmentioning
confidence: 51%
See 2 more Smart Citations
“…The attachment disorganization and DRD4 work was recently summarized well by Bernier and Meins [43], who posited a threshold approach to disorganization, arguing that when enough risk factors are encountered (genetic and environmental), disorganization results. A sample of Hungarian infants reported on by Gervai et al [44] and Lakatos et al [45,46] suggested that the 7-repeat DRD4 gene polymorphism could be a risk factor for disorganized attachment; specifically, the 7-repeat allele was observed in 71% of disorganized children in this sample, compared with only 29% of nondisorganized children. Further examination of the same sample revealed that this association was substantially enhanced when children also carried the -521T allele in the promoter region of the DRD4 gene [46].…”
Section: Advances In Relevant Gene-environment Considerationsmentioning
confidence: 51%
“…A sample of Hungarian infants reported on by Gervai et al [44] and Lakatos et al [45,46] suggested that the 7-repeat DRD4 gene polymorphism could be a risk factor for disorganized attachment; specifically, the 7-repeat allele was observed in 71% of disorganized children in this sample, compared with only 29% of nondisorganized children. Further examination of the same sample revealed that this association was substantially enhanced when children also carried the -521T allele in the promoter region of the DRD4 gene [46]. Children carrying both the 7-repeat allele and the -521T allele were 10 times more likely to present with disorganized attachment than their counterparts who carried neither risk allele.…”
Section: Advances In Relevant Gene-environment Considerationsmentioning
confidence: 51%
See 1 more Smart Citation
“…Infants carrying 7R-alleles might have more difficulty in adapting flexibly to irregular, abusive, or erratic parenting, which can then result in confusion and disorganization of attachment schemas. Indeed, prevalence of disorganized attachment is more than fourfold increased in children carrying the 7R-allele (Lakatos et al, 2000(Lakatos et al, , 2002Gervai et al, 2005;Van Ijzendoorn and Bakermans-Kranenburg, 2006;Gervai et al, 2007;Bakermans-Kranenburg et al, 2011). These findings are not consistent, however, and some studies report no associations between DRD4 genotypes and attachment (Luijk et al, 2011), while other demonstrate a positive association between the 7R-allele and secure attachment (Reiner and Spangler, 2010;Das et al, 2011).…”
Section: Da Receptor Configuration (D4-receptors)mentioning
confidence: 95%
“…Studying markers VNTR and -521 C/T and the novelty seeking trait in the Korean population including only females, Lee et al [9] showed that these parameters were higher in carriers of the C allele in the presence of the long VNTR allele. Lakatos et al [10] reported joint effect of these polymorphic markers on temperament traits in their study of attachment disorganization in infants. In a study of the combined effect of polymorphic markers -616 G/T and -521 C/T on variation of another trait correlating with novelty seeking, extraversion, in African Americans, Bookman et al [11] detected association of the CC genotype ( -521 C/T ) only in women.…”
Section: Introductionmentioning
confidence: 99%